A Cross-Species Comparative Approach to Positive Emotion Disturbance. (January 2017) - Gruber, June; Bekoff, Marc
Recent discoveries stress the importance of studying positive emotion disturbances (PED) yet there remains little empirical work or integrative conceptual framework in this domain. We suggest that an ideally suited opportunity to advance the study of PED is to consider a cross-species evolutionary framework. We apply this framework—drawing from principles of stabilizing selection—to recent empirical findings in humans and nonhumans suggesting how positive emotion and associated play behaviors may lead to detrimental outcomes. This cross-species approach suggests a potential paradigm shift in the way psychologists and evolutionary biologists approach positive emotion functioning, opening the possibility for new conceptual opportunities and interdisciplinary dialogues and research.